Rapid detection of Burkholderia cepacia complex carrying the 16S rRNA gene in clinical specimens by recombinase-aided amplification - Fu, Hanyu; Gan, Lin; Tian, Ziyan; Han, Juqiang; Du, Bing; Xue, Guanhua; Feng, Yanling; Zhao, Hanqing; Cui, Jinghua; Yan, Chao; Feng, Junxia; Fan, Zheng; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The Burkholderia cepacia complex (BCC) is a group of opportunistic pathogens, including Burkholderia cepacia, Burkholderia multivorans, Burkholderia vietnamiensis and Burkholderia ambifaria, which can cause severe respiratory tract infections and lead to high mortality rates among humans. The early diagnosis and effective treatment of BCC infection are therefore crucial. In this study, a novel and rapid recombinase-aided amplification (RAA) assay targeting the 16S rRNA gene was developed for BCC detection. The protocol for this RAA assay could be completed in 10 min at 39°C, with a sensitivity of 10 copies per reaction and no cross-reactivity with other pathogens. To characterize the effectiveness of the RAA assay, we further collected 269 clinical samples from patients with bacterial pneumonia. The sensitivity and specificity of the RAA assay were 100% and 98.5%, respectively. Seven BCC-infected patients were detected using the RAA assay, and three BCC strains were isolated from the 269 clinical samples. Our data showed that the prevalence of BCC infection was 2.60%, which is higher than the 1.40% reported in previous studies, suggesting that high sensitivity is vital to BCC detection. We also screened a patient with B. vietnamiensis infection using the RAA assay in clinic, allowing for appropriate treatment to be initiated rapidly. Together, these data indicate that the RAA assay targeting the 16S rRNA gene can be applied for the early and rapid detection of BCC pathogens in patients with an uncharacterized infection who are immunocompromised or have underlying diseases, thereby providing guidance for effective treatment.